The Optimum Location, Number and Size of Rice Mills in Tanjung Karang, West Malaysia - Siow, Kiat Foo (1990)
Non-linear programming is used in analysing the spatial equilibrium model to determine the optimum configuration of number, location and size of rice mills in Tanjung Karang, West Malaysia. The model simultaneously considered the costs of raw materials, handling, assembly, drying and milling and revenue from output to determine the optimum net industry revenue. In the model, the transportation cost, drying cost and milling cost were represented by 3 non-linear functions. The region covered in the study consists of 4 mills and 43 supply areas. A total of 16 configurations reflecting all possible combinations of mills and supply areas under existing conditions were constructed and analysed to yield 16 optimum solutions, one for each configuration. Configuration 15 had the highest net loss of $5,439,087 for 4 mills located at Sungai Besar, Sekinchan, ulu Tiram Buruk and Batu Dua with the respective mill sizes of 22,722 mt , 22,722 mt, 22,722 mt and 8,115 mt of paddy. The results of the analysis indicate the importance of assembly and processing costs in determining the optimum number, location and size of rice mills.